Uji Aktivitas Antihipertensi Ekstrak Dan Fraksi-Fraksi Daun Matoa Pada Tikus Jantan yang Diinduksi Angiotensin II dengan Parameter Kadar Renin dan Angiotensin II - Iyem Shahira; Jason Merari; Ika Purwidyaningrum (Jurnal Farmasi Indonesia, 2023)
ABSTRACT Matoa leaves (Pometia pinnata) is a plant thought to have hypertensive activity because it contains kuersetin. Research conducted by (Purwidyaningrum, 2017) extracts and fractions of matoa leaves has antihypertensive activity with an effective dose of 150 mg/kg. Other studies conducted by (Elisa, 2019) effects that can reduce blood pressure are extract doses of 300 mg and 30 mg of ethyl acetate fraction induced by angiotensin II can reduce systolic and diastolic blood pressure. This study aims to determine extracts and fractions of matoa leaves in decreasing renin levels and angiotensin II levels. The extraction method was maseration with 96% ethanol solvent and fractionated by liquids method using n-hexane solvent, ethyl acetate water. In this study used 21 male wistar strain rats divided into 7 groups, namely group I (normal), group II as negative control (CMC 1%), group III as positive control (Irbesartan), group IV (matoa leaves extract 60 mg/200g), Group V (fraction n-hexane 2,34 mg/200g), Group VI (ethyl acetate fraction 9,54 mg/200g), Group VII (water fraction 7,98 mg/200g). The results showed ethanol extract and matoa leaves fractions were not significantly difference in meaning with the positive control group different in reducing blood pressure, renin levels and angiotensin II induced by angiotensin II and were significantly from the normal and negative group. The water fraction (7,98 mg/200g) showed a decrease in systolic blood pressure of 9.0% and diastolic 7.1%, the ethyl acetate fraction showed a decrease in renin level 0f 23.6 %. EDM showed a decrease in 17.2% angiotensin II levels. Keyword : Pometia pinnata; renin levels; angiotensin II levels; induced angiotensin II